ANALISISA KADAR VITAMIN E DAN KAROTEN PADA RED PALM OIL DAN PALM OIL MENGGUNAKAN METODE DEEP FAT FRYING DENGAN VARIASI SUHU YANG BERBEDA - Pelawi, Yoga; Nur Ariyani Agustina; Imanuel Sembiring; Sinaga, Robert (Jurnal Agro Fabrica, 2025)
Palm oil and red palm oil are food ingredients that are rich in essential nutrients such as vitamin E and carotene. This study aims to analyze the levels of vitamin E and carotene in red palm oil and palm oil after deep fat frying with different temperature variations. The deep fat frying process was carried out at temperatures of 32°C, 180°C, 230°C and 280°C to determine the effect of temperature on the nutritional content. Analysis of vitamin E content was carried out using the UV-Vis spectrophotometry method, while analysis of carotene levels was carried out using the spectrophotometry method. The results showed that there was a decrease in vitamin E and carotene levels in both types of oil along with increasing frying temperature. A more significant decrease occurred at temperatures from 32°C to 180°C compared to temperatures from 230°C and 280°C. In addition, red palm oil has higher levels of vitamin E and carotene compared to palm oil at all temperature variations. These findings indicate the importance of considering temperature in the frying process to minimize nutrient loss in cooking oil, especially in oils with high vitamin E and carotene content such as red palm oil.